2003
DOI: 10.1046/j.1365-2273.2003.00685.x
|View full text |Cite
|
Sign up to set email alerts
|

Is it necessary to screen for hearing loss in the paediatric population with osteogenesis imperfecta?

Abstract: The aim of the study was to assess the necessity of a screening service to detect early hearing loss in the paediatric population with osteogenesis imperfecta. Twenty-two children were assessed over a 5-year period. Five children (22.7%) had normal hearing. Fourteen (63.6%) had conductive hearing loss, with 12 children in this group having otitis media with effusion (OME); all had resolution of hearing loss with appropriate therapy. Two children had persistent conductive losses unrelated to OME. Three children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
30
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 18 publications
3
30
0
1
Order By: Relevance
“…One recent study reported a prevalence of sensorineural hearing loss in 12% of ears, conductive hearing loss in 21% of ears, and mixed hearing loss in 29% of ears [18] in patients with OI. As has been reported in other investigations [17, 22], sensorineural hearing loss was present in a younger age group consisting of children (mean age = 9.87) and was found only in association with type I OI [18]. …”
Section: Hearing Loss In Osteogenesis Imperfectasupporting
confidence: 70%
See 4 more Smart Citations
“…One recent study reported a prevalence of sensorineural hearing loss in 12% of ears, conductive hearing loss in 21% of ears, and mixed hearing loss in 29% of ears [18] in patients with OI. As has been reported in other investigations [17, 22], sensorineural hearing loss was present in a younger age group consisting of children (mean age = 9.87) and was found only in association with type I OI [18]. …”
Section: Hearing Loss In Osteogenesis Imperfectasupporting
confidence: 70%
“…Slightly lower prevalence of hearing loss (50%) [19, 20] or even a higher prevalence of hearing loss (65–72%) [16, 21] has been reported. Methodological or definitional differences may account for the varying results across studies [22]. Some investigators have excluded cases of conductive hearing loss believed to be secondary to otitis media with effusion (OME) in younger patients with OI [16, 23] which would lead to underestimation of the prevalence of hearing loss.…”
Section: Hearing Loss In Osteogenesis Imperfectamentioning
confidence: 99%
See 3 more Smart Citations